Pengaruh Aplikasi Bokashi dan PGPR pada Pertumbuhan Stek Tanaman Apel (Malus domestica) - Kefi, Andreas; Marsianus Falo; Vinsensius Olin Kaet; Aseph Ikhsan Gumelar (Jurnal Hortikultura Indonesia, 2023)
Apple (Malus domestica) is a deciduous tree that is cultivated through vegetative propagation with grafting, trimmed and cuttings. Cuttings are mostly used as a method of reproduction because of the efficiency in time and price. In order to stimulate and accelerate the growth of the apple tree, the implementation of Plant Growth Promoting Rhizobacteria (PGPR) and bokhasi are used as breeding medium. This research is purposed to investigate the effect PGPR and breeding medium towards the growth of apple tree cuttings. This research is located in the farm of Eban village, West Miomaffo, TTU-NTT from 2nd February until 15th April 2022. This research design used Fully Randomized Design that consists of 2 factorials. The first factorial is Bokhasi Dosage (T) consists of 3 levels which are control (T0), 1:0,50 kg per polybag (T1), 1:0,75 kg per polybag (T2), 1:1 kg per polybag (T3). Meanwhile, the second factorial is Frequency PGPR (W) which consists of 3 levels; control (W0), once a week (W1), twice a week (W2), and trice a week (W3). The combination of the treatment consists of T0W0, T0W1, T0W2, T0W3, T1W0, T1W1, T1W2, T1W3, T2W0, T2W1, T2W2, T2W3, T3W0, T3W1, T3W2, T3W3, so that there are 16 treatment combination repeatedly for 3 times to get 48 experiment units. The result shows that the treatment combination level is 1:0.50 with the watering treatment level (W1) could increase the growth of roots in number, length, and to speed up the growth of apple leaves.Keywords: apple cutting, bokashi, PGPR